Сравнительный анализ различных конструкций индукционно-динамических систем при апериодическом разряде ёмкости на индуктор - Байда, Е.И. (Електротехніка і електромеханіка, 2011)
The article presents comparative analysis of different-type induction dynamic mechanisms speed. As an example, models of induction dynamic mechanisms without a magnetic core, with an open ferromagnetic core, and with a closed ferromagnetic core are considered. Quantitative and qualitative estimations are given.